2008
DOI: 10.1111/j.1447-0594.2008.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome after placement of a percutaneous endoscopic gastrostomy tube

Abstract: Mortality of patients who underwent percutaneous endoscopic gastrostomy appears to be high. In particular, the long-term prognosis was poor for patients with hypoalbuminemia, and this procedure is probably not preferred for patients with recurrent aspiration pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 22 publications
3
44
1
3
Order By: Relevance
“…In addition, low lymphocyte count was a risk factor for patients treated with PEG for malignant diseases. Previous studies did not evaluate long-term survival, but have indicated that the prognosis of PEG is influenced by several factors, including aging, sex, dementia, low serum albumin level, low serum cholesterol level, hyponatremia, and severe comorbidity including complicated pneumonia, cardiovascular diseases, and malignant diseases (2)(3)(4)(6)(7)(8)(9)(10)(11)(12). Judging from the one-year follow-up in the present study, nutritional status, as reflected by serum albumin level, might be crucial for survival after PEG, although rapid turnover proteins and other markers of nutritional status were not evaluated in the present retrospective study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, low lymphocyte count was a risk factor for patients treated with PEG for malignant diseases. Previous studies did not evaluate long-term survival, but have indicated that the prognosis of PEG is influenced by several factors, including aging, sex, dementia, low serum albumin level, low serum cholesterol level, hyponatremia, and severe comorbidity including complicated pneumonia, cardiovascular diseases, and malignant diseases (2)(3)(4)(6)(7)(8)(9)(10)(11)(12). Judging from the one-year follow-up in the present study, nutritional status, as reflected by serum albumin level, might be crucial for survival after PEG, although rapid turnover proteins and other markers of nutritional status were not evaluated in the present retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, PEG has been used mainly in patients with dysphagia caused by stroke and dementia. Only a few studies have evaluated the prognosis of patients with PEG, and some have indicated that a low serum albumin level might be a risk factor for stroke and dementia patients with PEG (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Murat Çakır ve arkadaşlarının yaptığı 700 hastadan oluşan bir çalışmada 600 hastanın (%85) nörolojik hastalığı olduğu bildirilmiştir [5]. Takunaga ve arkadaşlarının çalışmasında bu oran %75 olarak bulunmuştur [6]. Bizim çalışmamızda ise hastalarımızın 105'inde (%93) primer ya da sekonder nörolojik hastalık mevcuttu.…”
Section: Discussionunclassified
“…Bunların da çoğunluğu literatürle uyumlu olarak nörolojik problemi olan hastalardır. Yapılan çalışmaların bir kısmında, işlem süresi anestezi baş-langıcından itibaren ortalama 34 dakika olarak verilirken diğer çalışmalarda bu süre 7,5 dakika ile 13,2 dakika olarak bildirilmektedir [15][16][17]. Bizim çalışmamızda ortalama işlem süre-si 8,6±1,6 dakika (6-13 dakika) hesaplanmıştır.…”
Section: Gereç Ve Yöntemunclassified